Analysis of bioactive components and multi‐component pharmacokinetics of saponins from the leaves of Panax notoginseng in rat plasma after oral administration by LC–MS/MS. Issue 7 (18th January 2018) - Ju, Zhengcai; Li, Jia; Han, Han; Yang, Li; Wang, Zhengtao
Abstract: In this study, simple ultra‐high performance liquid chromatography coupled with quadrupole time‐of‐flight mass tandem mass spectrometry is used to characterize the absorbed components in rat plasma after the oral administration of saponins from the leaves of Panax notoginseng . Seventeen prototype compounds are structurally characterized. Furthermore, a simple and sensitive liquid chromatography with tandem mass spectrometry method is also used for the simultaneous determination of notoginsenoside Fc, ginsenoside Rb1, ginsenoside Rc, ginsenoside Rb3, ginsenoside Rd, and notoginsenoside Fe in rat plasma within 5 min. After n ‐butanol mediated liquid–liquid extraction, all analytes were separated on a C18 column and monitored in negative ion mode. Linearity, sensitivity, intra‐ and inter‐assay precision, accuracy, recovery, matrix effect, and stability were all within acceptable ranges. The validated liquid chromatography with tandem mass spectrometry method is successfully applied to the pharmacokinetic study of saponins from the leaves of Panax notoginseng in rats after oral administration. The results suggest that notoginsenoside Fc and ginsenoside Rb3 showed relatively higher exposure compared with other saponins. All saponins showed a long duration in plasma with a t 1/2 longer than 15 h, except notoginsenoside Fe ( t 1/2  = 2.78 h). This study provides important information about the metabolism of saponins from the leaves of Panax notoginseng, which is useful for completely understanding its mechanism of action.